Legal Effective of Putting "Business as Usual" Clause in Agreements - Marpi, Yapiter; Erlangga; Endaryono, Bakti Toni; Noviani, Krismayu (International Journal of Criminology and Sociology, 2021)
The development of business in Indonesia accompanies legal needs in the community, especially when triggered by the pandemic period of 2020, breakthroughs of business people to anticipate obstacles have made innovative clauses to be put in the agreement. The birth of the “business as usual” clause needs to be observed in this paper to study the legal impacts that may arise from its positive and negative aspects. This paper aims to analyze the impact of the agreement on the placement of a business as a usual clause on force majeure conditions and to examine the relevance of responsibility as good faith, its validity is limited so that risks can be minimized. This research paper use a random sampling method, normative-empirical legal research, socio-legal research tool types, data software through legal observations, analysis descriptions, modern or traditional agreement law reviews, and primary and secondary data collection. The results of this paper's research manifest the dispute resolution of the parties due to the agreement if it is not proven in good faith. This paper provides solutions and studies of the agreement law of business actors in an effective manner of responsibility and justice.